2017
DOI: 10.1080/17425255.2018.1417983
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of besifovir for the treatment of HBV infection

Abstract: Besifovir (LB80380) is a relatively new oral acyclic nucleotide phosphonate. We reviewed the pharmacokinetic characteristics of LB80380 and discussed its role in the treatment of chronic hepatitis B infection. Areas covered: LB80380 is a prodrug of LB80331 and LB80317. It is rapidly absorbed when taken orally. Escalating doses of besifovir produce linear increase of the plasma concentration. Doses above 60mg are effective for inhibiting HBV in human. Using 60mg as an example, the maximal concentration of LB803… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the bis‐POC derivative tenofovir ( 50 ) was recommended by the World Health Organization as first‐line treatment for adults with HIV infection . The acyclic nucleoside analogue known as besifovir or LB80380 ( 51 ) has reached phase II clinical trials for the treatment of chronic hepatitis B infection (Figure ) …”
Section: Prodrugs Containing a Phosphorus Atom In Their Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the bis‐POC derivative tenofovir ( 50 ) was recommended by the World Health Organization as first‐line treatment for adults with HIV infection . The acyclic nucleoside analogue known as besifovir or LB80380 ( 51 ) has reached phase II clinical trials for the treatment of chronic hepatitis B infection (Figure ) …”
Section: Prodrugs Containing a Phosphorus Atom In Their Structurementioning
confidence: 99%
“…ChemMedChem 2019, 14,190 -216 www.chemmedchem.org analoguek nown as besifovir or LB80380( 51)h as reached phase II clinicalt rials for the treatment of chronic hepatitis Bi nfection ( Figure 8). [32,34] 3. Bisphosphonates…”
Section: Prodrugs Containing Aphosphorus Atom In Their Structurementioning
confidence: 99%
“…In this study, the plasma exposure of the intermediate metabolite LB80331 and the active metabolite LB80317 increased as the degree of renal impairment increased after a single oral administration of 150‐mg besifovir dipivoxil (Figures 2A and 2C, and Table 3). In particular, the mean C max observed in the severe renal impairment group was no greater than those evaluated in an earlier study in healthy subjects after a single dose of 480‐mg besifovir dipivoxil, which showed no safety concerns, while exceeding the maximal concentration (397 ng/mL) observed in the lowest effective dose of 60 mg for inhibiting HBV in humans 11,12 …”
Section: Discussionmentioning
confidence: 70%
“…To assess the PK characteristics of LB80331 and LB80317, a single dose of besifovir dipivoxil was given to non‐HBV subjects with renal impairment. The intermediate metabolite LB80331 produced a linear increase in the AUC in the single‐dose range of 10 to 480 mg in healthy subjects; thus, the evaluation of its PK characteristics after a single dose is feasible 12 . Likewise, these characteristics were previously evaluated after a single dose of other drugs in the NRTI class: tenofovir disoproxil fumarate and adefovir dipivoxil 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In the liver cells it is phosphorylated to diphosphate and triphosphate forms, after which it competes with dGTP to bind with HBV DNA polymerase, and thus blocks the action of polymerase and inhibits viral proliferation. After the phase 2 clinical trial conducted by LG Life Sciences, Korea and the phase 3 clinical trial by Ildong Pharmaceutical, Korea, it was released on the market in 2017 as a domestic novel drug, with a similar efficacy to that of TDF, but without the latter's adverse side effect of reduced bone density (16).…”
Section: Besifovir (Lb80380)mentioning
confidence: 99%